2019
DOI: 10.1016/j.cub.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Population-Specific Selection on Standing Variation Generated by Lateral Gene Transfers in a Grass

Abstract: Graphical AbstractHighlights d Laterally acquired genes rapidly spread among established populations of a grass d Subsequent genomic erosion created neutral gene presenceabsence polymorphisms d One of these neutral genes was secondarily swept into a population d Lateral gene transfers have both direct and delayed adaptive impacts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 54 publications
(69 reference statements)
4
40
1
Order By: Relevance
“…The organelle phylogenetic trees recovered the seven major lineages reported in previous studies, as well as a clear incongruence between the two organelles (figure 1 and electronic supplementary material, figure S2 [10][11][12]). Indeed, six individuals, including one hexaploid and one dodecaploid, from Cameroon, Democratic Republic of Congo (DRC) and Zambia form a monophyletic group within plastid lineage DE, but form a paraphyletic group within mitochondrial lineage FG (electronic supplementary material, figure S2).…”
Section: (B) Time-calibrated Organelle Phylogeniessupporting
confidence: 64%
See 1 more Smart Citation
“…The organelle phylogenetic trees recovered the seven major lineages reported in previous studies, as well as a clear incongruence between the two organelles (figure 1 and electronic supplementary material, figure S2 [10][11][12]). Indeed, six individuals, including one hexaploid and one dodecaploid, from Cameroon, Democratic Republic of Congo (DRC) and Zambia form a monophyletic group within plastid lineage DE, but form a paraphyletic group within mitochondrial lineage FG (electronic supplementary material, figure S2).…”
Section: (B) Time-calibrated Organelle Phylogeniessupporting
confidence: 64%
“…The different photosynthetic types of A. semialata are associated with distinct ploidy levels in South Africa, but both C 4 and non-C 4 diploids exist in other parts of Africa [4,10], and nuclear genome analyses have found evidence of genetic exchanges between lineages with different photosynthetic types [11]. In addition, previously reported discrepancies between mitochondrial and plastid genomes [12] might reflect the footprint of intraspecific allopolyploidization, as previously suggested based on cytological analyses [13]. However, the history of nuclear exchanges and their effect on the spread of different photosynthetic types through ecological and geographical spaces remain to be formally established.…”
Section: Introductionmentioning
confidence: 99%
“…This underlines the 272 importance of HGT in diatoms and indicates that fixation of a laterally transferred gene takes place 273 quickly after the initial uptake. Indeed, in grasses it was recently shown that several plant-to-plant LGT 274 fragments were rapidly integrated and spread across the population, after which erosion occurred on 275 neutrally selected genes within those fragments 67 . 276…”
Section: Discussion 255mentioning
confidence: 99%
“…Such beneficial LGTs include those transferring functional genes that have undergone substantial modification through prolonged periods of positive selection in the donor genomes before being transferred (Christin et al., ). A gene that is selected for may also be accompanied by hitchhikers on the same fragment of foreign DNA, which can act as standing genetic variation for secondary selection (Olofsson et al., ). Lateral gene transfer thus provides a mechanism by which plants can effectively “steal” the genetic blueprints for molecular adaptation, thereby recycling the product of natural selection and altering the evolutionary trajectory of a species.…”
Section: Lateral Gene Transfers Represent Novel Mutations Of Major Fumentioning
confidence: 99%